The use of the environmental scan in health services delivery research: a scoping review protocol. Issue 9 (6th September 2019) - Charlton, Patricia; Doucet, Shelley; Azar, Rima; Nagel, Daniel A; Boulos, Leah; Luke, Alison; Mears, Kim; Kelly, Katherine J; Montelpare, William J
Abstract : Introduction: The environmental scan has been described as an important tool to inform decision-making on policy, planning and programme development in the healthcare sector. Despite the wide adoption of environmental scans, there is no consensus on a working definition within the health services delivery context and methodological guidance on the design and implementation of this approach is lacking in the literature. The objectives of this study are to map the extent, range and nature of evidence that describe the definitions, characteristics, conceptualisations, theoretical underpinnings, study limitations and other features of the environmental scan in the health services delivery literature and to propose a working definition specific to this context. Methods and analysis: This protocol describes a scoping review based on the methodology outlined by Khalil and colleagues. A comprehensive search strategy was developed by experienced health science librarians in consultation with the research team. A Peer Review of Electronic Search Strategies (PRESS) was completed. Two reviewers will independently screen titles, abstracts and full-text articles and select studies meeting the inclusion criteria from seven electronic databases: Academic Search Premier, Canadian Business & Current Affairs (CBCA), CINAHL, ERIC, Embase, MEDLINE and PsycINFO. The grey literature and reference lists of included articles will also be searched. The data will be analysed and presented in tabular format, and will include a descriptive numerical summary as well as a qualitative thematic analysis. Ethics and dissemination: This protocol provides an audit trail for a scoping review that will advance understanding about the environmental scan and its application in the health services delivery context. The review will propose a working definition and will inform future research to explore the development of a conceptual framework in this context. Findings will be disseminated through a peer-reviewed journal and conference presentations. The scoping review does not require ethics approval.